Batteries recycling process using local isolated thermopile culture - Jaapar, Jefri; Ahmad, Wan Azlina
Batteries are used daily in many portable electronic devices. Therefore spent batteries represent, within the wastes, an important environmental pollutant in terms of heavy metals content. Considering the risk associated with uncontrolled disposal of these batteries a legislation on disposal and recycling of spent batteries must be formulated.